DETECTING PATTERNS OF HYPERTENSION AMONG LIVE RELATED KIDNEY DONORS USING OFFICE AND AMBULATORY BP MONITORING: DATA FROM A TERTIARY CARE CENTER IN INDIA. (April 2021) - Aditya, Kapoor; Saklecha, Abhishek; Bhadauria, Dharmendra; Sahu, Ankit; Khanna, Roopali; Kumar, Sudeep; Garg, Naveen; Tewari, Satyendra; Goel, Pravin
Abstract : Objective: Live related renal donation is associated with significant benefits compared to cadaveric donations. Increase in BP, mild proteinuria, gestational HT, rare progression to ESRD and higher mortality among donors are important concerns. The aim of the study was to assess BP prior to surgery and 3–6 months later in healthy kidney donors using office BP measurement (OBPM) and ambulatory BP monitoring (ABPM). Figure. No caption available. Design and method: Voluntary kidney donors (n = 50, age > 18 years, age 48.72+ 12.49, 92% F) at a tertiary care institute in India were studied 1 week before nephrectomy & 3–6 months post surgery. BP definitions for OBP and ABPM were based on ESC 2018 guidelines. Results: Baseline OBP was 121.2+8.53/77.2+3.12 mm Hg; mean 24 hour ABPM was 115.74+16.84/65.22+13.1 mmHg. None of the subjects had HT on OBPM while 3/50 (6%) had high ABPM values. Three months post nephrectomy, mean OBP was 125.6+6.26/78.1+4.11 mm Hg; mean ABPM values were 118.21+14.61/67.11+ 12.4 mmHg. HT was documented in 8/50 (16%) on ABPM and two had HT by OBPM (grade 1 HT). Of the 3 subjects with high baseline ABPM, all had high ABPM at 3 months. Masked HT was observed in 6/50 (12%). At 6 months, 1more subject demonstrated stage 1 HT on OBPM (n = 3) and 10 (20%) had high ABPM values. Masked HT was noted in 7/50 (14%) and white coat HT in 1/50 (2%) Serum creatinine increased at 3 months (0.82 ± 0.13 vs 1.34 ± 0.18 mg/dl, p < 0.01), while at 6 months levels were similar to baseline (1.11 ± 0.16 mg/dl). A parallel trend in eGFR was observed (92.86 ± 19.1 ml/min, 79.9 + 15.4 ml/min, 87.8 + 14.5 ml/min, p = ns). Significant (>300 mg/day) proteinuria was noted in 5/50 donors at 3 months; all of them had hypertension on ABPM recordings. No new-onset proteinuria was observed at 6 months. Conclusions: High ABPM recordings are not uncommon in healthy kidney donors following surgery. At 3–6 months, 15–20% had high ABPM values; masked HT was observed in 14% and new onset proteinuria in 10%. Close follow up is mandatory in healthy kidney donors following surgery.